2018
DOI: 10.3389/fchem.2018.00402
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate Salts of Cytosine and Metformin: A Combined Experimental-Theoretical Study of Potential Metallodrugs Against Diabetes and Cancer

Abstract: Cytosine, a DNA and RNA building-block, and Metformin, the most widely prescribed drug for the treatment of Type 2 Diabetes mellitus were made to react separately with ammonium or sodium metavanadates in acidic aqueous solutions to obtain two polyoxovanadate salts with a 6:1 ratio of cation-anion. Thus, compounds [HCyt]6[V10O28]·4H2O, 1 and [HMetf]6[V10O28]·6H2O, 2 (where HCyt = Cytosinium cation, [C4H6N3O]+ and HMetf = Metforminium cation, [C4H12N5]+) were obtained and characterized by elemental analysis, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 101 publications
2
20
0
2
Order By: Relevance
“…Thus, POMs exhibit outstanding physical, chemical, and biochemical properties that remain to be completely understood and applied. Due to these properties, POMs are studied in environmental, chemical, and industrial fields, particularly in the areas of catalysis, corrosion prevention, smart glasses, and macromolecular crystallography, as well as in biology, such as for cancer treatment, bacterial infection, and diabetes, among others [1][2][3][4][5][6]. Although the number of POM studies with anticancer effects is increasing, their mechanisms of action in each type of cancer cell are still far from being understood [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, POMs exhibit outstanding physical, chemical, and biochemical properties that remain to be completely understood and applied. Due to these properties, POMs are studied in environmental, chemical, and industrial fields, particularly in the areas of catalysis, corrosion prevention, smart glasses, and macromolecular crystallography, as well as in biology, such as for cancer treatment, bacterial infection, and diabetes, among others [1][2][3][4][5][6]. Although the number of POM studies with anticancer effects is increasing, their mechanisms of action in each type of cancer cell are still far from being understood [3].…”
Section: Introductionmentioning
confidence: 99%
“…At pH around 1 and 25 °C, the half-life of decavanadate drops to about 6 s. At such strongly acidic conditions, the vanadate cation, VO 2 (H 2 O) 4 + , is the thermodynamically favorable species. The nature and concentration of the counterion also have a significant influence on the stability of the decavanadate polyanion along the pH range and the medium conditions, as indicated by the change of its decomposition rates in works of Soares et al and Gândara et al [134137].…”
Section: Transport Of Vanadium Species In Bloodmentioning
confidence: 99%
“…Also, the ratio of vanadium in the plasma to vanadium in RBCs increased over time with metavanadate administration but remained constant for decavanadate administration [162, 163]. Although there is still some disagreement regarding the extent of the physiological importance of the decavanadate ion, multiple recent studies have conclusively demonstrated that decavanadate can induce changes in the biological activities of several enzymes, which underlines the importance decavanadate-based compounds in medicine [86, 87, 9092, 134, 164167].…”
Section: Interconversion Between Vanadium Species and Cellular Redox mentioning
confidence: 99%
“…The past decades have marked important advances in the traditional view of many roles that metals and their compounds play in biological systems. In fact, metals, inorganic compounds and/or metals-organic frameworks show a diversity of properties that allowed them to present several and distinct biological, environmental and health applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recent insights into metals applications includes for instance, zinc nanoparticles as feed additives showing more efficiency than zinc salts, increasing growth not only in fish [1] but also in plants [2], besides preventing metal contaminants accumulation [2] and normalizing antioxidant biomarkers [1,2].…”
Section: Introductionmentioning
confidence: 99%